How Climate Changes Affects Mosquito Vector Competence In Dengue Virus Spread: A Literature Review - Farizqi, Lintan Kurnia (Journal of Diverse Medical Research: Medicosphere, 2024)
Background The impacts of climate change are currently increasing rapidly, largely due to greenhouse gas emissions from burning fossil fuels. Climatic conditions such as increased temperature, rainfall patterns affect the survival, development and geographical distribution of Aedes mosquitoes as well as their ability to transmit dengue virus known as vector competence. Dengue fever is transmitted by Aedes aegipty and Aedes albopictus mosquitoes. More than 10 million case if dengue fever have been reported. Climate change can accelerate the life cycle of mosquitoes, reducing the time it takes for the virus to develop inside the mosquito, increasing infection in the vector thus increasing the potential for dengue fever transmission. Methods This study uses the literature review method using the Google Scholar,Pubmed ans Science Direct databased using the keywords "climate change", "vector competence", "dengue fever"," Aedes aegypti","Aedes albopictus". Result Total 498 literature were found ( from Science direct , Pubmed and Google Scholar) then 9 articles were selected according to the specified topics and criteria. Conclusion Climate change has a significant impact on vector competence in Aedes mosquitoes in dengue virus transmission so that strategies in dengue fever control are needed. Keywords: Dengue, Climate change, Aedes aegypti, Aedes albopictus.